A collaborative study to establish the 3rd WHO International Standard for hepatitis B virus for nucleic acid amplification techniques. (March 2017) - Fryer, Jacqueline F.; Heath, Alan B.; Wilkinson, Dianna E.; Minor, Philip D.; ,
Abstract: Nucleic acid amplification techniques (NAT) are routinely used for clinical diagnostics and monitoring hepatitis B virus (HBV) infections, and are implemented on a voluntary basis for blood screening. A collaborative study was performed to evaluate a replacement WHO International Standard for HBV for the standardization of NAT. Two lyophilised HBV candidates were evaluated by 16 laboratories worldwide, alongside the existing HBV International Standard. The overall mean potency estimates for the candidate samples 1 and 2, relative to sample 3 (2nd HBV International Standard), from quantitative assays, were 5.93 and 5.98 log10 International Units (IU)/mL respectively. The variability in individual laboratory mean estimates for samples 1–3 for quantitative assays was ∼0.3 log10 IU/mL. The inter-laboratory variability for qualitative assays was higher. Accelerated thermal degradation studies indicate that both lyophilised candidates are stable and suitable for long-term use. Overall, the results suggested that both candidates were suitable as replacement International Standards. Sample 1 (NIBSC code 10/264) was established as the 3rd WHO International Standard for HBV for NAT with an assigned potency of 850, 000 IU/mL (∼5.93 log10 IU/mL), when reconstituted in 0.5 mL of nuclease-free water. It is intended for the calibration (in IU) of secondary reference materials used in HBV NAT.